(untitled) (Revista Sistemas de Producción Agroecológicos, 2012)
Two students of Agricultural Production, University of the Llanos, developed a project to use flour pepper (Capsicum annuum), as a source of carotenoids to mix with the concentrate for laying hens and watch these carotenoids contribute with the pigmentation of egg yolks produced by hens molted eighty-two (82) weeks, at a poultry farm (Agricultural Ocoa River) located at kilometer seven (7) track Villavicencio - Puerto López (Meta). To run the project, were randomly hundred twenty (120) layers and divided them into two groups. A control group consisting of twenty (20) to which hens were fed the commercial supplement and traditional management. An experimental group of one hundred (100) layers divided into five (5) sub-groups of twenty (20) layers each, which were given increasing amounts paprika flour in proportions of 0.5, 1.0, 1.5, 2.0 and 2.5% respectively. Furthermore, the work had an educational component for staff and operational managers poultry association Meta "AVIMETA" handlers eight (8) commercial egg-producing farms for consumption, in the department of Meta. To train operational staff, ran a process that included three (3) training strategies: A field demonstration, a training manual and three seminars. (A seminar for each work area where workers). Additionally, generated the appropriate space for the workers of the poultry farm "Agricultural Ocoa River" AVIMENTA policies and other poultry, could observe first hand, the results obtained in each of the three (3) weeks of that component of the work.